Maternal and fetal outcome of febrile morbidity in pregnancy at tertiary care level - K., Mamatha; Antony, Anjali; S., Nagaveni; B. C., Anusha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Fever in pregnancy is a common clinical problem worldwide. Effects of hyperthermia depends on the extent and duration of temperature elevation, timing of exposure in pregnancy and possibly on maternal nutritional status, comorbidities, medications, socio-economic background and several other factors. The exposure of maternal temperature has been reported to lead to cell disruptions, vascular disturbance and placental infarction which can lead to the risk of structural and functional defects in progeny. The underlying maternal cytokine polymorphism is strongly associated with both intrapartum fever and neonatal outcome. Hence there is a need to detect the various life-threatening medical complications of febrile morbidity leading to severe maternal morbidity and its impact on fetal outcome. Aim of study were to study the etiology of fever in pregnancy during the study period and to know the effect of fever on both the mother and the fetus. Methods: A prospective observational study. Results: Out of the 60 cases of fever in pregnancy, most common cause of fever was urinary tract infection (30%), followed by dengue fever (25%) and upper respiratory tract infection (23.3%). Fever was associated with complications as such PROM, PPROM, preterm labour, PPH, thrombocytopenia, anemia and abortions. Fetal outcome were preterm birth (25%), low birth weight (36%), neonatal sepsis (20%) and perinatal death (13.8%). Conclusions: Febrile morbidity in pregnancy leads to numerous maternal and fetal complications can occur due to fever in pregnancy from various causes. The most common cause of fever was UTI followed by dengue fever. The maternal and fetal complications can be avoidable if the cause for the fever is diagnosed and treated early.